Novas Saponinas Isoladas de Cereus jamacaru - Brito, Analu Freitas de Souza (2018)
Cereus jamacaru belongs to the family Cactaceae, is popularly known in Brazil by mandacaru, occurring in the states of Piauí, Paraíba, Ceará, Sergipe, Rio Grande do Norte, Alagoas, Pernambuco, Bahia and northern Minas Gerais. The popular use of this species is reported in the treatment of urethral problems, syphilis, pain in the cervical spine, being indicated also in the control of diabetes, in the treatment of vesicular stones, problems in the respiratory apparatus such as coughs and bronchitis, as well as ulcers. This work aimed to contribute to the expansion of the chemical knowledge of the genus Cereus through the phytochemical study of Cereus jamacaru. For this, the vegetable material, after drying and ground, was subjected to a maceration with 95% ethanol for 72 hours, this process being repeated three times to obtain the crude ethanolic extract (BSE). An aliquot of the BSE (30.0g) was subjected to a liquid-liquid partition in a separatory funnel with the solvents hexane, dichloromethane and ethyl acetate. The ethyl acetate fraction was subjected to column chromatography using Sephadex to perform a previous fractionation of this fraction. Then an analytical method was developed by HPLC-DAD for the analysis of fractions 5-10, later transposed to a semipreparative scale, thus it is possible to isolate a saponin (CJ1) reported for the first time in the literature. Afterwards, a method of isolation by HPLC-ESI-EM / EM was developed, thus it is possible to isolate another saponin (CJ2), also reported for the first time in the literature. In this way, this work revealed this species as a bioproducer of triterpene saponins.